Effective University Facility Management Plan Proposal Reflecting the Needs of the Main Users - Kim, Min Soo; Kim, Jun Ha (Frontiers in Psychology, 2020)
As the low birthrates in Korea intensify, the average school-age population is showing great reduction and the resources used for admission to the university are gradually decreasing as well, due to the continuing economic downturn. Therefore, in order for the university to remain competitive and keep up with the fast paced changes, it is very significant that they induce qualitative growth of university education and facilities through extensive and thorough analysis on the university facility management (UFM) for students who are the main users of university facilities. However, research done on university facilities in Korea has been focused mainly on space management, while the effective UFM reflecting in-depth opinions on the user class has been quite inadequate. Therefore, in order to improve student satisfaction and improve the efficiency of university facility management, it is crucial to understand the importance and status of the university facility management items. This way, an initial plan for improvement of university facility management considering the priorities that actively reflect the opinions of the students is prepared in this research. For the UFM items, the eight classifications of university facility management, which can be evaluated by users, and the details of the classifications are used for this research. For the UFM purposes, the first 176 performance indicators (PIs) are collected, consolidated and deleted. Finally, eight UFM purposes are derived. In order to find out which UFM items need more focus on, importance-performance analysis (IPA) is conducted. The priority of management is determined by where each factor is located on the grid. Additionally, multiple linear regression analysis is conducted to examine the effect of the importance value on the UFM items on the importance value on the UFM purposes. Finally, the average values of importance for the purpose of university facility management of two groups are compared and analyzed. As a result of the stages listed above, this research attempts to provide basic data on preparing the UFM plan. Therefore, it is possible to apply the method that reflects the needs of actual users in preparing future UFM plans throughout the research methods proposed in this research.